Top-down nanofabrication of silicon nanoribbon field effect transistor (Si-NR FET) for carcinoembryonic antigen detection - Bao Z (Dove Medical Press, 2017)
Zengtao Bao,1,* Jialin Sun,2,* Xiaoqian Zhao,2 Zengyao Li,2 Songkui Cui,2 Qingyang Meng,2 Ye Zhang,2 Tong Wang,2 Yanfeng Jiang3 1Department of Gastrointestinal Surgery, Lianyungang First People’s Hospital, Affiliated Hospital of the Clinical Medical School of Nanjing Medical University, Lianyungang, 2Department of Endoscopy Surgery, Wuxi People’s Hospital Affiliated to Nanjing Medical University, 3School of Internet of Things Engineering, Jiangnan University, Wuxi, People’s Republic of China *These authors contributed equally to this work Abstract: Sensitive and quantitative detection of tumor markers is highly required in the clinic for cancer diagnosis and consequent treatment. A field-effect transistor-based (FET-based) nanobiosensor emerges with characteristics of being label-free, real-time, having high sensitivity, and providing direct electrical readout for detection of biomarkers. In this paper, a top–down approach is proposed and implemented to fulfill a novel silicon nano-ribbon FET, which acts as biomarker sensor for future clinical application. Compared with the bottom–up approach, a top–down fabrication approach can confine width and length of the silicon FET precisely to control its electrical properties. The silicon nanoribbon (Si-NR) transistor is fabricated on a Silicon-on-Insulator (SOI) substrate by a top–down approach with complementary metal oxide semiconductor (CMOS)-compatible technology. After the preparation, the surface of Si-NR is functionalized with 3-aminopropyltriethoxysilane (APTES). Glutaraldehyde is utilized to bind the amino terminals of APTES and antibody on the surface. Finally, a microfluidic channel is integrated on the top of the device, acting as a flowing channel for the carcinoembryonic antigen (CEA) solution. The Si-NR FET is 120 nm in width and 25 nm in height, with ambipolar electrical characteristics. A logarithmic relationship between the changing ratio of the current and the CEA concentration is measured in the range of 0.1–100 ng/mL. The sensitivity of detection is measured as 10 pg/mL. The top–down fabricated biochip shows feasibility in direct detecting of CEA with the benefits of real-time, low cost, and high sensitivity as a promising biosensor for tumor early diagnosis. Keywords: silicon nanobiosensor, nanoribbon, field-effect transistor, carcinoembryonic antigen, microfluidic channel